Odpowiedź :
X(0,0) A(3,4)
[tex]|XA|=\sqrt{(3^{2}-0^{2} )+(4^{2}-0^{2} ) } =\sqrt{9+16}=\sqrt{25} =5[/tex]
X(0,0) B(1,3)
[tex]|XB|=\sqrt{(1^{2}-0^{2} )+(3^{2}-0^{2} )} =\sqrt{1+9}=\sqrt{10}[/tex]
X(0,0) C(-8,6)
[tex]|XC|=\sqrt{((-8)^{2} -0^{2} )+(6^{2} -0^{2} )} =\sqrt{64+36} =\sqrt{100} =10[/tex]
X(0,0) D(-3,-3)
[tex]|XD|=\sqrt{((-3)^{2} -0^{2} )+((-3)^{2} -0^{2} )} =\sqrt{9+9}=\sqrt{18}[/tex]
X(0,0) E(12,-5)
[tex]|XE|=\sqrt{(12^{2} -0^{2} )+((-5)^{2} -0^{2} )} =\sqrt{144+25} =\sqrt{169}=13[/tex]
Odpowiedź:
x= szukana odległość
A= (3,4) x= √(3²+4²)=5
B=(1,3) x=√(1²+3²)=√10
C= (-8,6) x=√[(-8)²+6²]=10
D= (-3,-3) x=√[(-3)²+(-3)²]=√18=3√2
E= (12,-5) x=√[12²+(-5)²]=13
Szczegółowe wyjaśnienie: